Support Your Recovery Needs (SYRN) - a systemic approach to improve sport performance - Adamczyk, J. G. (Biomedical Human Kinetics, 2023)
Study aim: The aim of this study was to present the Support Your Recovery Needs (SYRN) recovery system based on scientifi-cally confirmed methods, addressing the needs of athletes based on their subjective feelings of fatigue after training or competition.